THE EFFECT OF LEADERSHIP AND MOTIVATION ON TEACHER PERFORMANCE AND WORK COMMITMENT AS INTERVENING VARIABLES (CASE STUDY AT SMK BINA PENDIDIKAN 3 BOGOR) - Sutisna, Sajum; Djamil MZ, Masydzulhak; Iqbal , Ali (Dinasti Publisher, 2021)
This study aims to determine the effect of leadership and motivation on teacher performance with work commitment as an intervening variable at SMK Bina Pendidikan 3 Bogor. This research uses smartPLS version 3.0 software. with the existing analysis method that is explanatory, based on the initial hypothesis that this research consists of four variables, namely, leadership, motivation, commitment and teacher performance. From the results of research with the t hypothesis, the results of this study are work commitment has a positive and significant effect on teacher performance, leadership has a positive and significant effect on teacher performance, motivation has no effect on teacher performance, leadership has a positive and significant effect on work commitment, and motivation has a positive effect and significant to the work committee,